'They have come to Differing Opinions Because of their Differing Interpretations': Developing 16-19 Year-Old English Students' Understandings of Historical Interpretation Through On-line Inter-Institutional Discussion. (1st November 2012) - Chapman, Arthur
There is widespread agreement among history educators that history education should aim to help students understand and explore multiple perspectives on the past. However, as international research and theorizing indicates, understanding historical interpretations and accounts can present significant conceptual challenges for history students. This paper draws on data sets developed through a collaborative online project involving 16-19 year old history students, academic historians and an education academic in discussion about historical interpretations, in order to explore empirical questions about how these students conceptualized historical interpretations and about the extent to which student thinking changed during these discussions. The paper explores the impact that challenging historical tasks and questioning strategies and online interaction with expert historical thinkers can have in developing student thinking and reflects on the relevance of this project to broader questions relating to inter-sector and inter-institutional collaboration.